Workforce Diversity in Organizations: A Systematic Review with an Emphasis on Iranian Organizations - Davoudzadehmoghaddam , Alireza; Jafarinia, Saeed; Hassanpoor , Akbar; Vakili, Yousef (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Workforce diversity is an essential phenomenon in organizations. Statistics indicate a growing diversity among the workforce in Iran, particularly in terms of ethnic diversity. This study aims to examine work diversity through systematic review with an emphasis on Iranian Organizations. Methodology: This study employs the PRISMA method to review articles published on the management of diversity in organizations. Of the 140 identified Iranian and international articles, 59 relevant articles were selected. Most articles focus on gender diversity, and other causes of diversity, especially ethnic diversity, have received limited critical studies. Additionally, only a few articles address diversity management and its strategies in organizations, which represents a research gap. Findings: The research findings explored workforce diversity in four categories: the importance of diversity management; diversity management and communication; diversity management and organizational justice; diversity management and workforce productivity. Conclusion: The literature review demonstrated that workforce diversity is considered inevitable not only due to its positive organizational outcomes but also because of legal and ethical requirements in our contemporary world. Furthermore, it can be argued that the performance of diversity management at the organizational level has been overlooked. Notably, most researchers in the United States and Western European countries adopt quantitative approaches, highlighting the significance of qualitative approaches.